Vital pulp therapy in symptomatic immature permanent molars: Report of 3 cases - SheikhRezaie MS.; Amin Sobhani M.; Oloumi K. (Tehran University of Medical Sciences, 2009)
"nEndodontic treatment of immature permanent teeth accompanies with several issues. The primary goal when treating such teeth is to maintain pulp vitality so that root development can occur normally. Indications and requirements for vital pulp therapy include asymptomatic and reversible pulpitis. Also there are controversial opinions regarding the ultimate clinical treatment of the vital pulp therapy techniques. In this manuscript we report 3 cases of immature symptomatic permanent molars with irreversible pulpitis caused by caries exposure of the pulp that have been undergone vital pulp therapy successfully.